MANAJEMEN KINERJA APARATUR SIPIL NEGARA DI INDONESIA: SEBUAH KONSEP MANAJEMEN PUBLIK BARU - Bertha Lubis (GoAcademica Research dan Publishing, 2020)
New public management is a new concept in public administration science. This concept is results oriented, transparency and accountability of administrative services. Performance management is the key to results orientation. The Performance Management System is a record of the inputs, processes, outputs and results of government procedures. This helps to achieve the government's progress towards the goals. The Research goals to introduce the concept of performance management of the state civil servants in Indonesia as a new public management concept. The research used qualitative methods in the analysis of the research object. The results show that the bureaucracy that is complicated and still lacks quality of public services has become the curse of public administration science in Indonesia. The ASN performance management concept as a new performance-based public management is a breakthrough that can improve ASN performance which in the end has an impact on the performance of public services.